Taxonomy of the Quedius mukuensis group (Coleoptera: Staphylinidae: Staphylinini: Quediina) with descriptions of four new species from China - Cai, Yan-Peng; Zhao, Zong-Yi; Zhou, Hong-Zhang (Zootaxa, 2015)
Four new species of the subgenus Microsaurus Dejean, 1833 of the genus Quedius Stephens, 1829 are described based on specimens collected from China: Q. (Microsaurus) indigestus sp. nov., Q. (Microsaurus) purus sp. nov. and Q. (Microsaurus) rectus sp. nov. from Sichuan, and Q. (Microsaurus) medius sp. nov. from Hubei. The new species all belong to the Quedius mukuensis group, which is now increased to a total of 16 species. Line drawings and color illustrations of the adults, and the genitalia of the new species and some other ones are given. A key to all the species of this group is provided.